1986
DOI: 10.1177/00220345860650101501
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Streptococcus sanguis Adhesion to Artificial Pellicle

Abstract: Studies of equilibria between Streptococcus sanguis and artificial pellicle have suggested that there are multiple binding sites for the organism. In the present study, adhesion of S. sanguis to saliva-coated hydroxylapatite was examined by means of kinetic methods. Cell-pellicle complex formation was measured from initiation of binding to equilibrium. Rate constants were calculated for forward reactions (adsorption) and reverse reactions (desorption). Initial binding obeyed reversible, first-order kinetics, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 27 publications
2
44
0
1
Order By: Relevance
“…This suggests that the initial encounter with the pellicle substratum is slow enough to be studied and slow enough to be inhibited. Whereas sialic acid probably has a role in'the binding reaction (12), the initial binding equilibrium seems to be largely independent of a specific high-affinity receptor (8). The rate constants for adsorptiQn and desorption in this initial equilibrium show a marked dependence on temperature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that the initial encounter with the pellicle substratum is slow enough to be studied and slow enough to be inhibited. Whereas sialic acid probably has a role in'the binding reaction (12), the initial binding equilibrium seems to be largely independent of a specific high-affinity receptor (8). The rate constants for adsorptiQn and desorption in this initial equilibrium show a marked dependence on temperature.…”
Section: Resultsmentioning
confidence: 99%
“…However, that specificity has been difficult to define, and it is believed that multiple forces govern adhesion (10)(11)(12). Kinetic studies suggest that S. sanguis passes through two distinct binding transitions (8). The first stage is a reversible one described by pseudofirst-order rate constants for adsorption and desorption.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the biofilm form on the different pellicles might be different for different types of samples. In addition, it has been suggested that the adhesion of bacteria is affected by various factors, such as the differences in the charge of the surface layer of the bacteria 70) , van der Walls and electrostatic forces, hydrophobicity and the presence of lectin ligands 71) . Another study will be necessary to understand the reasons why S. mutans adhered more to Co-Cr than the other alloys.…”
Section: Factors Affecting the Adhesion Of Biofilms To The Framework mentioning
confidence: 99%